What do we know about the effects of mental training applied to combat sports? A systematic review - Andreato, L. V.; dos Santos, M. G.; Andrade, A. (Psychology of Sport and Exercise, 2022)
Objectives This study aimed to investigate the effects of mental training applied to combat sports athletes.